2015
DOI: 10.1002/ejic.201500227
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed Functionalization of the Thenoyltrifluoroacetone Coligands by Aromatic Dyes in Bis(cyclometallated) IrIII Complexes: From Phosphorescence to Fluorescence?­

Abstract: The synthesis, characterization and photophysical properties of a series of neutral Ir(C ∧ N-Meppy) 2 (O ∧ O-tta-Ar) (MeppyH = 4-methyl-2-phenylpyridine; tta = thenoyltrifluoroacetonate) complexes containing new functionalized tta-Ar ligands in which the incorporated Ar group is an aromatic dye such as naphthalene, pyrene, naphthalimide or coumarin, are reported. The arylated proligands ttaH-Ar are readily obtained in two steps through Pd-catalyzed C-H bond activation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…[1,9,17,23,24,26,27] The complexes containing β-diketonate ligands as L^L chelates are an important part of this family of emitters. [5,[28][29][30][31][32] These type of compounds differ from the other complexes containing neutral chelates (for example, aromatic diimines) by zero complex charge and stronger (covalent/electrostatic) binding to metal center. The simplest from the synthetic viewpoint and widely used β-diketonate ligands are symmetrical and do not contain the substituents with developed aromatic systems, [8,29,32,33] that prevents effective contribution of these ligands into MLCT or LC excited states due to high energy of their LUMO orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…[1,9,17,23,24,26,27] The complexes containing β-diketonate ligands as L^L chelates are an important part of this family of emitters. [5,[28][29][30][31][32] These type of compounds differ from the other complexes containing neutral chelates (for example, aromatic diimines) by zero complex charge and stronger (covalent/electrostatic) binding to metal center. The simplest from the synthetic viewpoint and widely used β-diketonate ligands are symmetrical and do not contain the substituents with developed aromatic systems, [8,29,32,33] that prevents effective contribution of these ligands into MLCT or LC excited states due to high energy of their LUMO orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the spectra of the four compounds are similar, which is consistent with almost identical DFT-calculated HOMO−LUMO gaps (3.13−3.18 eV). In contrast, the groups of Ziessel and Castellano 23 and Doucet and Guerchais 24 have observed that the incorporation of a polyaromatic fragment to the β-diketonate ligand of related 2-phenylpyridine complexes has a dramatic influence on the photophysical properties of the resulting iridium derivatives. Vibronic structure of the spectra, particularly in MeTHF at 77 K, is consistent with the contribution of ligand-centered 3 π−π* transitions to the excited states in addition to 3 MLCT.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Since the Claisen condensation is accompanied by formation of side products, purification of a diketone is usually difficult. Steam distillation of the reaction mixture followed by precipitation of metal (Cu, Mg, Mn, Fe) chelates and their acidic decomposition [2223] or preparative chromatography [3334] were used to obtain a pure product. We have found that in most cases, simple vacuum distillation of the crude reaction mixture is sufficient to obtain pure β-diketones with fluorinated side-chain.…”
Section: Resultsmentioning
confidence: 99%